Development of a procedure for determining the basic parameter of aquatic ecosystems functioning ‒ environmental capacity - Isaienko, Volodymyr; Madzhd, Svitlana; Pysanko, Yana; Nikolaiev, Kyrylo; Bovsunovskyi, Evgen; Cherniak, Larysa (Eastern-European Journal of Enterprise Technologies, 2019)
Environmental capacity as the main parameter of functioning of aquatic ecosystems was studied. This parameter is an effective indicator of violation of structural and functional processes in the technogenically altered water body. The adapted conceptual model of the system of indicators Actions - State - Consequences was applied. In accordance with the developed classification of the system of indicators, balance of environmental capacity of the aquatic ecosystem serves as a part of the integral indicator of state of the aquatic ecosystem, as a consequence of effect of exogenous factors of anthropogenic origin. Due to the use of integrated indicator systems, it was possible to provide not only qualitative but also quantitative characteristics of the environmental capacity. Estuary of a medium peneplain river which is the most representative part of the river and reflects consequences of anthropogenic effects occurring in the river basin was selected as a study object. Taking into account the hierarchical pattern of levels of water systems development, the study of the state of medium rivers at a local level will enable development of water conservation measures that will contribute to improvement of water quality in large rivers. The developed procedure can be successfully adapted to other technogenically altered peneplain rivers. The results of the performed mathematical calculations were presented in a form of graphs of dependence of environmental capacity and techno-capacity on numerous parameters of the aquatic ecosystem functioning. Dynamics of changes in these parameters in 2009‒2017 was demonstrated. The study results indicate that biota adapted to a certain level of technogenic pollution and environmental capacity was stable (27‒37) in the period of 2012‒2016 which shows optimal conditions for existence of the aquatic ecosystem. The generalized estimation of changes over the whole period of studies suggests that the loss of environmental capacity (decreased to 13.3) was caused by excessive technogenic impact on the river aquatic ecosystem which predetermines formation of techno-capacity. As a result, a reduction in the level of remaining ecological reserve necessary for restoration of a technogenically altered aquatic ecosystem of the river was observed